Analyses of land cover change of Singkil Swamp Wildlife Reserve in the last 20 years. (May 2020) - Onrizal, O; Maulana, M I
Abstract: Singkil Swamp Wildlife Reserve (SSWR) is remaining tropical coastal forested wetland in west coast of Sumatra. The conservation area is also facing habitat loss and destruction due to illegal activities, such as logging and land conversion. However, there is no data available on land cover change of important habitat of great ape critically endangered, Sumatran orangutan ( Pongo abelii ). This study aimed to determine the rate of change in land cover of the SSRW and to analyze the factors causing these changes in the last 20 years using landsat image. Land cover classification was carried out using supervised classification with maximum likelihood approach. The result showed that primary swamp forest area of the SSWR continued to experience a significant decline every year during the period 1998-2018 that around 24% of primary swamp forest was lost in the period due to deforestation and degradation. Therefore, degraded forests of SSWR should immediately be rehabilitated to restore ecological functions and to increase their productivity as well as education program to increase awareness coupled with forest monitoring and law enforcement to reduce illegal activities. Finally, appropriate management should be applied with co-management between government and local communities in conserving the important conservation areas.